Rhythmic glucose metabolism regulates the redox circadian clockwork in human red blood cells - Ratnasekhar Ch (Nature Portfolio, 2021)
Red blood cells, which do not possess a nucleus, have circadian redox rhythms with incompletely understood regulatory mechanisms. Here the authors show that glucose metabolism plays a crucial role in regulating circadian redox status of human red blood cells.